The Phenomenon of Aging and Discourses on Old Age in the Context of Typification and Stereotypes - Sedat Doğan (Senectus)
This article focuses on the problem of the extent to which a given discourse on old age can encompass the phenomenon of aging in terms of the possibilities and limits of typification. The transition from phenomenon to discourse is made possible within this linguistic structure through typification as an activity in which type concepts are produced and reproduced. This article emphasizes the existence of a semantic gap between phenomenon and discourse and how typification functions as an interpretation to close this gap. The article argues that during typification, which is obligatory due to the nature of language, a particular type of concept that can close the above-mentioned gap comes to the fore at the expense of other alternatives and compresses the phenomenon towards a particular discourse. In the case of aging and old age, this situation occurs when aging, which is a completely singular experience, is squeezed into discourses on chronological and biological old age. The aim of the article is to question the possibility of a research practice that does not erase singularity in terms of the possibilities and limits of typification.